The Management of Acute Uncomplicated Cystitis in Adult Women by Family Physicians in Canada. Issue 4 (2008) - McIsaac, Warren J; Prakash, Preeti; Ross, Susan
Abstract : INTRODUCTION: There are few Canadian studies that have assessed prescribing patterns and antibiotic preferences of physicians for acute uncomplicated cystitis. A cross-Canada study of adult women with symptoms of acute cystitis seen by primary care physicians was conducted to determine current management practices and first-line antibiotic choices. METHODS: A random sample of 2000 members of The College of Family Physicians of Canada were contacted in April 2002, and were asked to assess two women presenting with new urinary tract symptoms. Physicians completed a standardized checklist of symptoms and signs, indicated their diagnosis and antibiotics prescribed. A urine sample for culture was obtained. RESULTS: Of the 418 responding physicians, 246 (58.6%) completed the study and assessed 446 women between April 2002 and March 2003. Most women (412 of 420, for whom clinical information about antibiotic prescriptions was available) reported either frequency, urgency or painful urination. Physicians would have usually ordered a urine culture for 77.0% of the women (95% CI 72.7 to 80.8) and prescribed an antibiotic for 86.9% of the women (95% CI 83.3 to 90.0). The urine culture was negative for 32.8% of these prescriptions. The most commonly prescribed antibiotic was trimethoprim/sulfamethoxazole (40.8%; 95% CI 35.7 to 46.1), followed by fluoroquinolones (27.4%; 95% CI 22.9 to 32.3) and nitrofurantoin (26.6%; 95% CI 22.1 to 31.4). CONCLUSION: Empirical antibiotic prescribing is standard practice in the community, but is associated with high levels of unnecessary antibiotic use. While trimethoprim/sulfamethoxazole is the first-line empirical antibiotic choice, fluoroquinolone antibiotics have become the second most commonly prescribed empirical antibiotic for acute cystitis. The effect of current prescribing patterns on community levels of quinolone-resistant Escherichia coli may need to be monitored.